The Influence of Product Quality, Reputation, and Trust on Purchasing Decisions at PT Semarak Konstruksi Batam - Andriyani, Baiq Dewi; Realize, Realize (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Currently, the development of infrastructure such as roads, bridges and other facilities continues to increase along with population growth. This research is based on consumer complaints regarding product quality. The purpose of this study was to determine the effect of product quality, reputation and trust on purchasing decisions at PT Semarak Konstruksi Batam. The object of this research is consumers of PT Semarak Konstruksi Batam. The sampling technique used non-probability sampling. Data processed using SPSS 25. The analysis method used is descriptive statistical test, validity test and reliability test, classical assumption test, influence test and hypothesis testing. Based on the results of the study, it shows that product quality, reputation and trust partially have a positive and significant effect on purchasing decisions at PT Semarak Konstruksi Batam. Based on the anova test with the value of f count> f table and sig <0.05. It can be concluded that the variables of product quality, reputation and trust have a positive and significant influence on purchasing decisions.